2020
DOI: 10.1111/jomf.12667
|View full text |Cite
|
Sign up to set email alerts
|

Transactional Associations Between Couple Relationship Intimacy and Depressive Symptoms Across 10 Years

Abstract: Objective This study tested a transactional model of associations between couple relationship intimacy and one's own and one's partner's depressive symptoms across 10 years. Background Depressive symptoms and couple relationship intimacy are important aspects of individual functioning and family well‐being. Partners' mental health and experiences in couple relationships may be interdependent. Method Six waves of data from the National Institute of Child Health and Human Development Study of Early Child Care an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…Without a positive therapeutic treatment alliance, individual depressive symptoms seemed to spill over into interpersonal areas, such as couple satisfaction (Whisman & Baucom, 2012). The finding is consistent with adult psychotherapy research suggesting that depressive symptoms are precursors of relationship distress, especially for males (Yan, Schoppe‐Sullivan, & Feng, 2020). Conversely, when the therapeutic relationship was high, males with high couple satisfaction initially rated their relationship as more satisfying at session four, compared to those with less satisfied baseline relationships.…”
Section: Discussionsupporting
confidence: 88%
“…Without a positive therapeutic treatment alliance, individual depressive symptoms seemed to spill over into interpersonal areas, such as couple satisfaction (Whisman & Baucom, 2012). The finding is consistent with adult psychotherapy research suggesting that depressive symptoms are precursors of relationship distress, especially for males (Yan, Schoppe‐Sullivan, & Feng, 2020). Conversely, when the therapeutic relationship was high, males with high couple satisfaction initially rated their relationship as more satisfying at session four, compared to those with less satisfied baseline relationships.…”
Section: Discussionsupporting
confidence: 88%
“…The subsequent negative prospective (between waves) effect of husbands' decreases in perceived marital support on husbands' pessimism points to a harmful reinforcing cycle for men and suggests husbands' dependence on their wives' support (Segel‐Karpas & Ermer, 2021). This effect echoes a recent finding that for husbands, but not wives, increased levels of depression predicted a decrease in perceived marital intimacy (Yan et al., 2020).…”
Section: Discussionsupporting
confidence: 85%
“…Hence, it is possible that women can balance their husbands' decreased support and draw on external social resources to preserve their outlook on life, but men's greater focus on the marital relationship as a main source of interaction makes them more susceptible to drops in perceived marital support. However, the sensitivity of women's future expectations to changes in perceived marital support requires further exploration, as one study found women's depressive symptoms decreased after they experienced increases in marital intimacy (Yan et al., 2020). This finding, however, was based on a sample of younger couples, who are at the stage of forming families and raising children; during this phase in the family cycle, wives may more strongly depend on their husbands' support than in later, post child‐rearing phases (Manuel et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence of differences in marital abuse and marital quality that differ across race even after controlling for income (Lockhart 1987; Bulanda and Brown 2007). Moreover, because relational intimacy in a marriage is tied with mental health, specifically depression (Yan, Schoppe‐Sullivan, and Feng 2020), then differences in the incidence of abuse will propagate into mental health outcomes. Finally, prior research has also pointed out the limitations of traditional measures of family structure, particularly among blacks (Mouzon 2013).…”
Section: Resultsmentioning
confidence: 99%